Cosmic Intelligence as a Transformative Approach for Primary Education Teachers in the Age of Artificial Intelligence: A Conceptual Framework - Moh Aniq Khairul Basyar Basyar; Irvan Mahendra (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The rapid proliferation of Artificial Intelligence (AI) technologies across all sectors of civilization has created unprecedented demands on primary education teachers, who are now expected to not only master technological tools but to fundamentally reimagine their pedagogical identities. This conceptual article introduces Cosmic Intelligence as a transformative framework for primary education teachers in the AI era for which an integrative construct that synthesizes existential awareness, ethical reasoning, systems thinking, and adaptive wisdom in response to the cosmic-scale disruptions generated by AI. Drawing on Howard Gardner's theory of Multiple Intelligences, particularly his eighth and ninth intelligences (naturalist and existential), alongside contemporary literature on AI-integrated pedagogy, teacher professional development, and educational transformation, this study proposes a conceptual model of Cosmic Intelligence comprising five interrelated dimensions: (1) Existential Awareness, (2) Adaptive Technological Wisdom, (3) Ethical-Relational Intelligence, (4) Holistic Systems Thinking, and (5) Transcendent Purpose Orientation. A qualitative research design using library research and conceptual analysis methodology is employed to construct and validate this framework. Findings suggest that Cosmic Intelligence addresses a critical gap in current AI-era teacher competency frameworks, which tend to prioritize technical skills while neglecting deeper ontological and ethical dimensions of teaching. This article contributes a novel theoretical lens through which teacher education programs can be redesigned to cultivate teachers who are not merely AI-literate but cosmically intelligent — capable of guiding young learners through civilizational transformation with wisdom, empathy, and transcendent purpose.